Competence-oriented technology for long-term athletic development of young ice hockey players - Sukhachev, E. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate and practically develop a competence-based technology for the long-term sports training of young ice hockey players aged 7-17, ensuring the alignment of goals, content, methods, and performance criteria within the system of long-term athletic development.